Assessment of total and soluble fluoride content in commercial dentifrices in Davangere: A cross sectional survey - D J Veeresh; Umesh Wadgave (Wolters Kluwer Medknow Publications, 2014)
Introduction: The major reason for decline in dental caries across globe is because of widespread use of fluoride dentifrices. For a fluoride dentifrice to be effective in the control of dental caries, an adequate concentration of the fluoride must be soluble. Objective: To assess soluble fluoride and total fluoride content in selected commercial dentifrices in Davangere. Materials and Methods: The soluble fluoride and total fluoride content in six selected commercial dentifrices in Davangere were assessed and expressed as ppm of fluoride (F) (mgF/g). Total fluoride and soluble fluoride was determined using an ion-specific electrode. Descriptive statistics applied to assess the mean total fluoride and soluble fluoride. Results: The total fluoride and soluble fluoride concentrations were approximately near to 1,000 ppm. Among the six dentifrices evaluated, four contained sodium fluoride (NaF) and two contained sodium monofluorophosphate (Na MFP) as fluoride compound. Conclusions: All the fluoridated dentifrices evaluated in this study contain adequate amount of soluble and total fluoride.